2022
DOI: 10.1007/s12035-022-03034-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Spinal 5-HT3 Receptor and Spinal Dorsal Horn Neuronal Excitability Alleviates Hyperalgesia in a Rat Model of Parkinson’s Disease

Abstract: Pain in Parkinson's disease (PD) is increasingly recognized as a major factor associated with poor healthrelated quality of life. However, classic therapeutic drugs supplying dopamine have limited therapeutic effect on PD related pain. This suggests that there is a mechanism outside the dopamine system that causes pain in PD. Our previous study has demonstrated that 6-OHDA induced PD model manifested hyperalgesia to thermal and mechanical stimuli and decreased serotonin (5-HT) contents in the spinal dorsal hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…These data are reminiscent of data from primates, showing that MPTP, which primarily kills DA neurons in the brain, fails to cause extensive changes in gut motility or may even increase it [63]. Additionally, previous sensory testing revealed increased sensitivity to heat or pin-point pressure in rats lesioned with 6-OHDA [64,65], another traditional method of inducing dopaminergic cell loss in the SNpc. However, PD patients show increased sensitivity to cold pain most consistently [52].…”
Section: Discussionmentioning
confidence: 53%
“…These data are reminiscent of data from primates, showing that MPTP, which primarily kills DA neurons in the brain, fails to cause extensive changes in gut motility or may even increase it [63]. Additionally, previous sensory testing revealed increased sensitivity to heat or pin-point pressure in rats lesioned with 6-OHDA [64,65], another traditional method of inducing dopaminergic cell loss in the SNpc. However, PD patients show increased sensitivity to cold pain most consistently [52].…”
Section: Discussionmentioning
confidence: 53%
“… 75 For example, intrathecal injection of 5-HT3 receptor antagonists significantly attenuated mechanical nociceptive hyperalgesia and thermal nociceptive hypersensitivity in 6-hydroxydopamine lesioned rats. 76 The effectiveness of 5-hydroxytryptamine reuptake inhibitors in the treatment of various clinical pain conditions (eg fibromyalgia) further demonstrates the involvement of 5-HT receptors in pain regulation. 77 , 78 In genetic studies, polymorphisms in monoamine metabolism and transport have been shown to correlate with the diagnosis or severity of fibromyalgia, such as serotonin 5-HT 2A receptor and 5-HT transporter.…”
Section: The Underlying Mechanisms Of Sleep Deprivation Exacerbating ...mentioning
confidence: 99%
“…The 5-HT7 receptor plays a role in regulating essential physiological processes such as circadian rhythms, the sleep-wake cycle, thermoregulation, learning and memory formation, and nociception [146]. Additionally, the expression of 5-HT7 has been identified in spinal cord [147], liver [148], immune system cells [123,149], heart, and kidneys [150].…”
Section: -Ht7 Receptorsmentioning
confidence: 99%